Microbiology of respiratory system infections. Volume 1. / [edited by] Kateryna Kon; Mahendra Rai - Kon, Kateryna
The Microbiology of Respiratory System Infections reviews modern approaches in the diagnosis, treatment, and prophylaxis of respiratory system infections. The book is very useful for researchers, scientists, academics, medical practitioners, graduate and postgraduate students, and specialists from pharmaceutical and laboratory diagnostic companies. The book has been divided into three sections according to the types of respiratory pathogens. The first section contains reviews on the most common and epidemiologically important respiratory viruses, such as influenza virus, severe acute respiratory system coronavirus, and recently discovered Middle East respiratory syndrome coronavirus. The second section is devoted to bacterial and fungal pathogens, which discusses etiology and pathogenesis including infections in patients with compromised immune system, and infections caused by fungal pathogens, such as Aspergillus and Pneumocystis. The third section incorporates treatment approaches against different types of bacterial infections of the lower respiratory tract. This section reviews classical antimicrobial and phytomedical approaches as well as the application of nanotechnology against respiratory pathogens.